1999
DOI: 10.1046/j.1468-2982.1999.019002095.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Crossover Assessment of Blood Pressure Following Administration of Avitriptan, Sumatriptan, Or Placebo To Patients with Mild To Moderate Hypertension

Abstract: We examined the effects of avitriptan, a 5-hydroxytryptamine 1-like (5HT1) receptor agonist for the treatment of migraine, in patients with medicated, controlled, mild to moderate hypertension relative to placebo and sumatriptan. The study was randomized, double-blinded, placebo-controlled, and 4-way crossover in design. Twenty patients (12M, 8F) participated. As required by protocol, all were stable on medications for mild to moderate hypertension, with a supine diastolic blood pressure of < 95 mmHg. Qualifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In our trial, elevated blood pressure was the most commonly reported adverse event in all three groups, but it occurred most frequently in the sumatriptan group. Previously published trials reported similar findings for sumatriptan in healthy subjects or migraineurs without hypertension [22] and in hypertensive patients who were being treated with antihypertensive medications [23]. Four patients in the sumatriptan group experienced chest‐related symptoms.…”
Section: Discussionsupporting
confidence: 60%
“…In our trial, elevated blood pressure was the most commonly reported adverse event in all three groups, but it occurred most frequently in the sumatriptan group. Previously published trials reported similar findings for sumatriptan in healthy subjects or migraineurs without hypertension [22] and in hypertensive patients who were being treated with antihypertensive medications [23]. Four patients in the sumatriptan group experienced chest‐related symptoms.…”
Section: Discussionsupporting
confidence: 60%
“…22 For this reason, studies of the effects of triptans on blood pressure, whether with healthy volunteers or those with controlled hypertension, were performed on otherwise healthy volunteers with no history of migraine. 11,16 In general, the treatments administered in this study were well tolerated. Almotriptan had no effect on pulse or electrocardiographic parameters; these results are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 91%
“…This is illus- trated by the profound effects observed for avitriptan after administration in 1 of 4 subjects with uncontrolled hypertension in a clinical trial. 11 The concern for the triptans during development is whether these agents produce profound blood pressure effects in patients with hypertension controlled by medication. The pharmacokinetic characteristics of migraineurs for the triptan agents were not different from those of healthy volunteers; the only effects observed were a delayed time to peak plasma concentrations during the migraine, and these were generally modest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation